2014
DOI: 10.1073/pnas.1319743111
|View full text |Cite
|
Sign up to set email alerts
|

Induced multipotency in adult keratinocytes through down-regulation of ΔNp63 or DGCR8

Abstract: The roles of microRNAs (miRNAs) and the miRNA processing machinery in the regulation of stem cell biology are not well understood. Here, we show that the p53 family member and p63 isoform, ΔNp63, is a transcriptional activator of a cofactor critical for miRNA processing (DGCR8). This regulation gives rise to a unique miRNA signature resulting in reprogramming cells to multipotency. Strikingly, ΔNp63 −/− epidermal cells display profound defects in terminal differentiation and express a subset of markers and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
126
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(133 citation statements)
references
References 33 publications
7
126
0
Order By: Relevance
“…Our RNAPII ChIP-seq and RNA-seq data at the TP63 gene locus showed that Δ Np63 is the main isoform during keratinocyte differentiation, whereas the expression of the TAp63 isoform was not detected (Supplementary Fig S1D). These data are consistent with results from a recent RNA-seq analysis of the developing mouse epidermis [53] and from p63 isoform-specific knockout experiments that demonstrated the major functional role of ΔNp63 in the epidermis [54, 55]. These observations do not however rule out the possibility that the TAp63 isoform is expressed at an extremely low level, and the expression might be detected with deeper sequencing.…”
Section: Discussionsupporting
confidence: 87%
“…Our RNAPII ChIP-seq and RNA-seq data at the TP63 gene locus showed that Δ Np63 is the main isoform during keratinocyte differentiation, whereas the expression of the TAp63 isoform was not detected (Supplementary Fig S1D). These data are consistent with results from a recent RNA-seq analysis of the developing mouse epidermis [53] and from p63 isoform-specific knockout experiments that demonstrated the major functional role of ΔNp63 in the epidermis [54, 55]. These observations do not however rule out the possibility that the TAp63 isoform is expressed at an extremely low level, and the expression might be detected with deeper sequencing.…”
Section: Discussionsupporting
confidence: 87%
“…TAp63 is also expressed in response to stresses such as wound healing (Su et al 2009b). DNp63 plays a major role in mediating the effects of p63 on epidermal development, whereas TAp63 keeps stem cells within the skin in quiescence to avoid early depletion of these cells and suppresses tumorigenesis in postnatal epidermis (Su et al 2009b;Romano et al 2012;Chakravarti et al 2014).…”
Section: The P53 Family and Its Isoformsmentioning
confidence: 99%
“…Global effects of p63 on microRNAs are realized via direct regulation and transactivation of the Dicer promoter by TAp63 (Su et al 2010) and the DiGeorge syndrome critical region gene 8 (DGCR8) promoter by DNp63 (Chakravarti et al 2014). In addition, p63 negatively regulates expression of several microRNAs of the miR-34 family, which show reciprocal expression patterns with p63 in the epidermis (Antonini et al 2010).…”
Section: Va Botchkarev and Er Floresmentioning
confidence: 99%
“…Here, the DNp63a-DGCR8 pathway was shown to inhibit the expression of a unique miRNA signature that mediates the reprogramming of cells to multipotency and induces miRNAs that initiate terminal differentiation, including miR-205 and members of the miR-34 and miR-200 families. DNp63a, but not DNp63g, is able to transactivate the DGCR8 promoter (26).…”
Section: Dn Variants Act As Crucial Regulators Of Emtmentioning
confidence: 90%